2022
DOI: 10.2343/geochemj.gj22006
|View full text |Cite
|
Sign up to set email alerts
|

Mineralogy and geochemistry of pitchblende in the Changjiang U ore field, Guangdong Province, South China: Implications for its mineralization

Abstract: The Changjiang U ore field developed typical granite-related U mineralization in the Zhuguangshan complex, China. Pitchblende is the most important ore mineral in these mineralizations. In this study, the mineralogy and geochemistry of pitchblende were investigated by electron probe microanalysis (EPMA) and laser ablation inductively coupled plasma mass spectrometry (LA-ICP-MS) to identify the genesis of the Changjiang U ore field. Pitchblende exhibits colloidal, fragmented, spherulitic and fine-grained crysta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 66 publications
0
1
0
Order By: Relevance
“…Considering the textural and compositional characteristics and the hydrothermal origin of the uranium-rich inclusions studied in the fluorite samples from the La Azul mine, these can be defined as pitchblende. The results obtained are chemically very similar to the pitchblende reported by the authors of [63] in a hydrothermal system. Figure 10 compares the chemical results obtained for uraninite from the La Azul mine with those of pitchblende obtained by these authors.…”
Section: Uranium Mineralogysupporting
confidence: 88%
See 1 more Smart Citation
“…Considering the textural and compositional characteristics and the hydrothermal origin of the uranium-rich inclusions studied in the fluorite samples from the La Azul mine, these can be defined as pitchblende. The results obtained are chemically very similar to the pitchblende reported by the authors of [63] in a hydrothermal system. Figure 10 compares the chemical results obtained for uraninite from the La Azul mine with those of pitchblende obtained by these authors.…”
Section: Uranium Mineralogysupporting
confidence: 88%
“…The name uraninite is essentially used for the crystalline (isometric) uranium dioxide (UO 2 ) mineral with low water content, while the name pitchblende refers to the microcrystalline or colloform amorphous variety, with its water content varying from about 2 per cent to 5 per cent. The small grain size may be attributed to rapid crystallization at low temperatures in mesothermal deposits, e.g., [63,64].…”
Section: Uranium Mineralogymentioning
confidence: 99%
“…Furthermore, the whole-rock and mineral geochemistry defined a magmatic-hydrothermal genetic model directly related to the intrusion of early Yanshanian granites in the Nanling belt. Zhong et al (2023) [20] studied the chronology and petrogenesis of the dikes of the Lujing uranium ore field and found that the Mesozoic dikes provided a favorable oxidation reduction interface and secondary structure fractures for a uranium ore-forming space. However, to our knowledge, only a few studies have been conducted on the granitic dikes around the Huayangchuan deposit, with minimal investigations of the genetic relationship between granitic magmatic activity and U-Nb-REE mineralization [21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%